2022
DOI: 10.3390/nu14102177
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Brain Proteins for Bitter-Sweet Taste Perception: A Joint Proteome-Wide and Transcriptome-Wide Association Study

Abstract: Objective: Bitter or sweet beverage perception is associated with alterations in brain structure and function. Our aim is to analyze the genetic association between bitter or sweet beverage perception and human brain proteins. Materials and methods: In our study, 8356 and 11,518 proteins were first collected from two reference datasets of human brain proteomes, the ROS/MAP and Banner. The bitter or sweet beverage perception-related proteome-wide association studies (PWAS) were then conducted by integrating rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Contrary to the similarity in the direction of expression for Olfr1286 in both regions, Tmem245 was downregulated in male NAcore compared to the upregulation in the male PFC. Tmem245 has been linked with schizophrenic psychosis ( 51 ), which is similar to psychostimulant-induced psychosis ( 52 ). Here, we hypothesize a region-dependent role for Tmem245 in facilitating psychosis-like behavior during cocaine withdrawal linked with increasing the likelihood of seeking cocaine during periods of abstaining cocaine intake.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the similarity in the direction of expression for Olfr1286 in both regions, Tmem245 was downregulated in male NAcore compared to the upregulation in the male PFC. Tmem245 has been linked with schizophrenic psychosis ( 51 ), which is similar to psychostimulant-induced psychosis ( 52 ). Here, we hypothesize a region-dependent role for Tmem245 in facilitating psychosis-like behavior during cocaine withdrawal linked with increasing the likelihood of seeking cocaine during periods of abstaining cocaine intake.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that caffeine consumption should be reduced during pregnancy and that it would be advisable to start an awareness program to avoid these negative consequences on the child's development. The association between taste sensitivity and alterations in brain structures and functions was also studied by Wei et al [34]. These authors analyzed the genetic association between the perception of sweet or bitter beverages and human brain proteins, since the perception of a bitter or sweet drink is associated with alterations in brain structure and function [35,36].…”
mentioning
confidence: 99%